Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12933-022-01469-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liraglutide vs. lifestyle changes on soluble suppression of tumorigenesis-2 (sST2) and galectin-3 in obese subjects with prediabetes or type 2 diabetes after comparable weight loss

Abstract: Background Soluble suppression of tumorigenesis-2 (sST2) and galectin (Gal)-3 are two biomarkers related to inflammation, metabolic disturbances and to myocardial fibrosis that characterize several cardiac pathological conditions. Increased circulating levels of these molecules have been associated with risk of cardiovascular death. Treatment with liraglutide, a glucagon-like peptide 1 analog, is associated with weight loss, improved glycemic control, and reduced cardiovascular risk. We wanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Clinical and biochemical baseline characteristics of the study subjects have been previously presented [ 12 , 13 , 16 ] and relevant variables are shown in Table 1 . Patients randomized to liraglutide treatment and lifestyle intervention were similar on most parameters, except for triglycerides (TG), waist circumference and visceral adipose tissue (VAT) being higher in the liraglutide arm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and biochemical baseline characteristics of the study subjects have been previously presented [ 12 , 13 , 16 ] and relevant variables are shown in Table 1 . Patients randomized to liraglutide treatment and lifestyle intervention were similar on most parameters, except for triglycerides (TG), waist circumference and visceral adipose tissue (VAT) being higher in the liraglutide arm.…”
Section: Resultsmentioning
confidence: 99%
“…In clinical trials, liraglutide reduces levels of various inflammatory cytokines such as tumor necrosis factor (TNF) and interleukin (IL)-6 in overweight and obese individuals with T2DM [ 9 11 ]. We have previously shown that the inflammatory marker soluble suppression of tumorigenesis-2 (sST2) was decreased after weight loss induced by liraglutide treatment, but not after comparable weight loss due to lifestyle changes [ 12 ]. Interestingly, in the same cohort, liraglutide achieved a more pronounced reduction in visceral adipose tissue (VAT) and improvement in beta cell function, independently of weight loss [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effects of LGT, it has been reported that it would reduce Gal-3 levels in the liver of an obese animal model ( Tølbøl et al, 2018 ). However, Simeone et al (2022) recently reported that LGT treatment did not affect circulating Gal-3 levels in obese patients. In accordance, we did not observe changes in Gal-3 expression in VAT in response to LGT administration.…”
Section: Discussionmentioning
confidence: 96%
“…The objective of clinical research in the field is to help manage diabetes, promote cardiovascular health, reduce cardiovascular adverse events, and improve the long-term prognosis ( 9 13 ). The research mainly involves drug treatment and management ( 12 ), lifestyle intervention ( 14 ), and other aspects.…”
Section: Introductionmentioning
confidence: 99%
“…When developing a COS, we should follow the COS-STAR guidelines ( 28 ), the COS-STAP guidelines, and the handbook for developing COS. As the outcomes in cardiovascular diabetology are complex ( 12 14 ), potential modification of the steps will be performed based on the characteristics of cardiovascular diabetology in order to develop a high-quality COS. In the current paper, we report the methodological framework and hope it will help other researchers in this field.…”
Section: Introductionmentioning
confidence: 99%